Understanding Sustainable Construction Practices in Reducing Environmental Impacts and Enhancing Infrastructure Performance in Developing Countries - Susanti Djalante; Ranno Marlany Rachman; Tryantini Sundi Putri; Nini Hasriyani Aswad; Agustan Agustan (Mandalika Institute, 2026)
Developing countries face the dual challenge of rapid infrastructure expansion and escalating environmental degradation, yet established sustainable construction frameworks remain largely predicated on developed-economy assumptions. This library research aims to understand how regionally adapted sustainable construction practices can simultaneously reduce environmental impacts and enhance infrastructure performance in developing countries. Through systematic content analysis of peer-reviewed journal articles, institutional reports, and case study documents spanning Asia, Africa, and Latin America, the study identifies practices including compressed stabilised earth bricks, rice husk-based materials, bamboo construction, laterite bricks, and nature-based solutions. Findings demonstrate CO₂ reductions of 75–88%, with some innovations achieving carbon-negative performance, alongside enhanced seismic resilience, improved thermal performance, and cost reductions up to 40%. Persistent economic, technical, and institutional barriers require coordinated policy intervention. The research concludes that contextually adapted sustainable construction offers a viable pathway for developing nations to achieve infrastructure development aligned with environmental sustainability and the Sustainable Development Goals.